KOMBINASI PUPUK KANDANG DAN NPK PLUS TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Aliumascalonicum. L) VARIETAS FILIPINA - Sulaiman Sulaiman; Anis Sholihah; Indiyah Muwarni (AGRONISMA, 2021)
The cultivation of shallots (Allium ascalonicum. L) is an alternative cultivation system to reduce the use of inorganic chemical fertilizers developed in order to produce healthy horticultural products free from harmful organic compounds and have high yield quality. Therefore, this study aims to determine the effect of a combination of doses of organic manure and NPK Plus on the growth and production of shallots. This study is a land experiment using a factorial randomized block design (RAK) with controls. There are two factors tested, namely factor 1 is the dose of various types of manure consisting of 3 levels: 20, 20 and 20 tons/h-1 and the second factor is the dose of NPK plus fertilizer on plant growth and production